Glimpses of Indian women in the freedom struggle - Mohanty, Jyotsnamoyee (New Delhi : Discovery Pub. House, 1996)
With reference to Orissa.
Includes bibliographical references (p. [175]-184) and index.
Keywords: Women -- Political activity -- India -- Odisha; Nationalism -- India -- Odisha -- History; Odisha (India) -- Politics and government